Priority-setting in agricultural research for poverty reduction, nutrition improvement and resilience. - Masters, William. (Tufts University. Tisch Library., 2018)
Presented at the Agricultural and Applied Economics Association, August 2017. This presentation focuses on agricultural R & D and its return as a public investment.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy